Reaction of the Soviet Union and Hungary to the UN Actions in the Hungarian Question - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Principal contributor(s): United Nations Special Committee on the Problem of Hungary UN Special Committee analysis of the reaction of the official Soviet and Hungarian press to the UN Special Committee Report. The reaction of both governments was manifested in attacks against the Committee of Five, the convening of the Special Session and the report itself. It is noted that while Soviet criticism, with one exception, is of a general nature, while the Hungarians attempt to refute certain specific parts of the Report, and even quote from it.